Detection of phenazepam in illicitly manufactured Erimin 5 tablets. Issue 2 (8th July 2016) - Lim, Wendy J.L.; Yap, Angeline T.W.; Mangudi, Merula; Koh, H.B.; Tang, Angeline S.Y.; Chan, K.B.
Abstract : A validated ultra‐high‐performance liquid chromatographic (UHPLC) method was used to determine the phenazepam dosage in clandestinely produced Erimin 5 tablets. Tablets from five different seizures submitted to the laboratory in 2013 were found to have a dosage of about 2.4 milligrams. The measurement uncertainty of the assay was estimated to be 3.2 % (relative) at a coverage factor of k=2. As an adjunct study the dyes in the tablets from several seizures were determined by thin‐layer chromatography (TLC) for future comparative studies.